Prevalence of Beta-Lactam and Quinolone/Fluoroquinolone Resistance in Enterobacteriaceae From Dogs in France and Spain—Characterization of ESBL/pAmpC Isolates, Genes, and Conjugative Plasmids - Dupouy, Véronique; Abdelli, Mouni; Moyano, Gabriel; Arpaillange, Nathalie; Bibbal, Delphine; Cadiergues, Marie-Christine; Lopez-Pulin, Diego; Sayah-Jeanne, Sakina; de Gunzburg, Jean; Saint-Lu, Nathalie; Gonzalez-Zorn, Bruno; Andremont, Antoine; et al. (Frontiers in Veterinary Science, 2019)
Quantitative data on fecal shedding of antimicrobial-resistant bacteria are crucial to assess the risk of transmission from dogs to humans. Our first objective was to investigate the prevalence of quinolone/fluoroquinolone-resistant and beta-lactam-resistant Enterobacteriaceae in dogs in France and Spain. Due to the particular concern about possible transmission of extended-spectrum cephalosporin-resistant isolates from dogs to their owners, we characterized the ESBL/AmpC producers collected from dogs. Rectal swabs from 188 dogs, without signs of diarrhea and that had not received antimicrobials for 4 weeks before the study, were quantified for total and resistant Enterobacteriaceae on selective media alone or containing relevant antibiotic concentrations. Information that might explain antimicrobial resistance was collected for each dog. Extended-spectrum cephalosporin-resistant isolates were subjected to bacterial species identification (API20E), genetic lineage characterization (MLST), ESBL/pAmpC genes identification (sequencing) and plasmid characterization (pMLST). Regarding beta-lactam resistance, amoxicillin- (AMX) and cefotaxime- (CTX) resistant Enterobacteriaceae were detected in 70% and 18% of the dogs respectively, whereas for quinolone/fluoroquinolone-resistance, Nalidixic acid- (NAL) and ciprofloxacin- (CIP) resistant Enterobacteriacea were detected in 36% and 18% of the dogs, respectively. Medical rather than preventive consultation was a risk marker for the presence of NAL and CIP resistance. CTX resistance was mainly due to a combination of specific ESBL/pAmpC genes and particular conjugative plasmids already identified in human patients: blaCTX-M-1/IncI1/ST3 (n = 4), blaCMY-2/IncI1/ST12 (n=2) and blaCTX-M-15/IncI1/ST31 (n=1). blaSHV-12 (n=3) was detected in various plasmid lineages (InI1/ST3, IncI1/ST26, and IncFII). ESBL/AmpC plasmids were located in different genetic lineages of E. coli, with the exception of 2 strains in France (ST6998) and 2 in Spain (ST602). Our study highlights dogs as a potential source of Q/FQ-resistant and ESBL/pAmpC-producing bacteria that might further disseminate to humans, and notably a serious risk of future acquisition of CTX-M-1 and CMY-2 plasmids by the owners of dogs.